Preference Of Dental Practitioner On Antibiotic Prophylaxis For Infective Endocarditis Guidelines: The Cohort Of Klang Valley - Ahmad Tarmidzi, Nor Azura; Mohamed Ramli, Nalisha; Ghazali , Norzalina; Mohd Isa, Mohd Nazrin; Hakim@Abdul Khakin, Ammar Yaseer bin Abdul (IIUM Medical Journal Malaysia, 2017)
Introduction: Antibiotic prophylaxis guidelines for infective endocarditis have been regularly revised and modified based on current scientific evidence. These guidelines commonly regarded as standard of care and determine the medicolegal standards. The aim of this study was to elicit the current practice of prophylaxis antibiotic for Infective endocarditis among general dental practitioner in Klang Valley. Materials and Methods: A standardized questionnaire forms were distributed to the selected dental practitioners in Klang Valley by mail. Results: 43 out of 427 questionnaires was answered and posted back. 70.6% of the respondent claimed to be following guidelines that advocate antibiotic prophylaxis for the prevention of infective endocarditis (American Heart Association, British Cardiac Society, European Society of Cardiology) while others claimed to be following The National Institute for Health and Clinical Excellence guidelines (no antibiotic prophylaxis). However, majority of the respondent showed poor compliance towards the guideline. Several barriers have been identified. Conclusion(s): Majority of the respondent preferred to choose AHA guidelines for antibiotic prophylaxis. However, adherence to the guidelines seems to be low. Efforts to increase awareness of the guidelines among the dental practitioner should be taken.